N,N'-(Hexane-1,6-diyl)bis(4-methyl-N-(oxiran-2-ylmethyl)benzenesulfonamide): Synthesis via cyclodextrin mediated N-alkylation in aqueous solution and further Prilezhaev epoxidation - Fischer, Julian; Millan, Simon; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2013)
N-alkylation of N,N'-(hexane-1,6-diyl)bis(4-methylbenzenesulfonamide) with allyl bromide and subsequent Prilezhaev reaction with m-chloroperbenzoic acid to give N,N'-(hexane-1,6-diyl)bis(4-methyl-N-(oxiran-2-ylmethyl)benzenesulfonamide) is described. This twofold alkylation was performed in aqueous solution, whereby α-, and randomly methylated β-cyclodextrin were used as adequate phase transfer catalysts and the cyclodextrin–guest complexes were characterized by 1H NMR and 2D NMR ROESY spectroscopy. Finally, the curing properties of the diepoxide with lysine-based α-amino-ε-caprolactam were analyzed by rheological measurements.
Keywords: alkylation; cyclodextrins; epoxy; rheology; sulfonamides

(untitled) - Klee, J. E.; Flammersheim, H.-J. (Macromol. Chem. Phys., 2002)

Polymeric Materials Encyclopedia - Klee, J.; Hörhold, H.-H. (Epoxide-amine addition polymers, linear, 1996)

(untitled) - Wang, L.; Wu, Y.; Zhang, W.; Kannan, K. (Environ. Sci. Technol., 2012)

(untitled) - Resende, L. M.; Rached-Junior, F. J. A.; Versiani, M. A.; Souza-Gabriel, A. E.; Miranda, C. E. S.; Silva-Sousa, Y. T. C.; Sousa Neto, M. D. (Int. Endodont. J., 2009)

(untitled) - Fenouillot, F.; Rousseau, A.; Colomines, G.; Saint-Loup, R.; Pascault, J.-P. (Prog. Polym. Sci., 2010)

(untitled) - Chiu, Y.-C.; Chou, I. C.; Tseng, W.-C.; Ma, C.-C. M. (Polym. Degrad. Stab., 2008)

(untitled) - Shikha, D.; Kamani, P. K.; Shukla, M. C. (Prog. Org. Coat., 2003)

(untitled) - Tao, Z.; Yang, S.; Chen, J.; Fan, L. (Eur. Polym. J., 2007)

U.S. Patent - Pews, R. G. (Diepoxide derivatives of N,N*-disubstituted disulfonamides, 2006)

(untitled) - Kolman, A.; Chovanec, M.; Osterman-Golkar, S. (Mutat. Res., 2002)

(untitled) - Braun, D.; Lee, D. W. (Angew. Makromol. Chem., 1976)

(untitled) - Braun, D.; Lee, D. W. (Angew. Makromol. Chem., 1977)

(untitled) - Prileschajew, N. (Ber. Dtsch. Chem. Ges., 1909)

(untitled) - Woods, K. W.; Beak, P. (J. Am. Chem. Soc., 1991)

(untitled) - Mimoun, H. (Angew. Chem., Int. Ed. Engl., 1982)

(untitled) - Ritter, H.; Tabatabai, M. (Prog. Polym. Sci., 2002)

(untitled) - Alupei, V.; Alupei, I. C.; Ritter, H. (Macromol. Rapid Commun., 2005)

(untitled) - Wenz, G. (Angew. Chem., Int. Ed. Engl., 1994)

(untitled) - Surendra, K.; Krishnaveni, N. S.; Sridhar, R.; Rao, K. R. (Tetrahedron Lett., 2006)

(untitled) - Zhang, Q.; Cheng, G.; Huang, Y.-Z.; Qu, G.-R.; Niu, H.-Y.; Guo, H.-M. (Tetrahedron, 2012)

(untitled) - Yamaguchi, I.; Osakada, K.; Yamamoto, T. (Macromolecules, 1997)

(untitled) - Li, W.; Zhang, W.; Ma, X.; Wang, P.; Du, M. (Appl. Catal., A: Gen., 2012)

(untitled) - Stetter, H.; Roos, E.-E. (Chem. Ber., 1954)

(untitled) - Müller, A.; Sauerwald, A. (Monatsh. Chem., 1927)

(untitled) - Tewari, Y. B.; Miller, M. M.; Wasik, S. P.; Martire, D. E. (J. Chem. Eng. Data, 1982)

(untitled) - Philippe, C.; Milcent, T.; Crousse, B.; Bonnet-Delpon, D. (Org. Biomol. Chem., 2009)

(untitled) - Brotzel, F.; Chu, Y. C.; Mayr, H. (J. Org. Chem., 2007)

(untitled) - Brotzel, F.; Mayr, H. (Org. Biomol. Chem., 2007)

WO Patent - Frost, J. W. (Synthesis of Caprolactam from Lysine, 2005)